2013
DOI: 10.1088/1748-9326/8/3/035050
|View full text |Cite
|
Sign up to set email alerts
|

Situated lifestyles: II. The impacts of urban density, housing type and motorization on the greenhouse gas emissions of the middle-income consumers in Finland

Abstract: The relationship between urban form and greenhouse gas (GHG) emissions has been studied extensively during the last two decades. The prevailing paradigm arising from these studies is that a dense or compact urban form would best enable low-carbon living. However, the vast majority of these studies have actually concentrated on transportation and/or housing energy, whereas a growing number of studies argue that the GHG implications of other consumption should be taken into account and the relationships evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 37 publications
1
53
0
1
Order By: Relevance
“…The spatial availability of consumer spaces, together with their visual-cultural environment aiming to persuade people to spend more [7] (p. 151), influence expenditure choices and consequently increase the environmental load imposed by residents from higher hierarchy levels. Significant increases in the purchase of services, but not necessarily tangible goods, along with urbanization featuring equalized income levels have been illustrated in earlier research [52,63].…”
Section: Discussionmentioning
confidence: 81%
“…The spatial availability of consumer spaces, together with their visual-cultural environment aiming to persuade people to spend more [7] (p. 151), influence expenditure choices and consequently increase the environmental load imposed by residents from higher hierarchy levels. Significant increases in the purchase of services, but not necessarily tangible goods, along with urbanization featuring equalized income levels have been illustrated in earlier research [52,63].…”
Section: Discussionmentioning
confidence: 81%
“…Upper-income urban residents in the United States and Europe tend to consume more imported goods and services, fly more often, and drive out of the city more often than people living on lower incomes 7 . In the United Kingdom, during the explosion of lowcost air travel from the late 1980s to the early 2000s, the number of working-class passengers flying out of London increased by around 60%; wealthy passengers' trips increased by nearly 150%.…”
Section: Farther Afieldmentioning
confidence: 99%
“…They argued that energy efficiency improvements cannot reduce energy demand as much as expected [45,46]. The energy rebound effect was confirmed by some other studies [47][48][49][50][51][52]. A recent study showed that the residential household energy rebound effect aroused by efficiency improvement is comparatively small in China [52].…”
Section: Results and Discussion Of Lmdi Modelmentioning
confidence: 84%